Optimization of Samapta Unit Patrols to Prevent the Criminal Act of Theft by Weighing the Jurisdiction of Sragen Polres - Silitonga, Christopher (Advances in Police Science Research Journal, 2024)
This final project is motivated by the large number of criminal acts of theft with increasing weight at the Sragen Police in the last 5 years. and analyzing the management of the patrol organization of the Samapta Unit at the Sragen Police, and also describing and analyzing the organizational resources of the Samapta Unit in carrying out patrols for nozzles in the jurisdiction of the Sragen Police. As an analytical knife, it uses POAC management theory and resource theory, and uses SWOT theory to solve the factors that affect patrol conditions. It is also supported by the concepts of optimization, patrolling, and nozzles. This final project uses a qualitative approach with a case study research method with collection techniques. data through interviews with Sragen Police personnel, field observations, and document studies. This final project explores in terms of management and resources, which was found to be still not optimal when using the perkabaharkam guidelines No. 1 of 2017 and related police regulations, especially in terms of management planning patrol routes that are not in accordance with actuating or implementing, evaluating and monitoring as well not optimal. In terms of resources, deficiencies were also found, especially in terms of people and methods. In accordance with the capacity of a unit commander, officers can optimize patrols in terms of management and resources with innovations both in terms of management by making patrol books, and monitoring through electronic media, as well as in terms of resources where it is necessary to increase the ability of patrol members and optimize the right methods .